2021
DOI: 10.3390/biology10111090
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Enhancement of Protein Disulfide Isomerase-like Activity of a Cyclic Diselenide Conjugated with a Basic Amino Acid by Inserting a Glycine Spacer

Abstract: In a previous study, we reported that (S)-1,2-diselenane-4-amine (1) catalyzes oxidative protein folding through protein disulfide isomerase (PDI)-like catalytic mechanisms and that the direct conjugation of a basic amino acid (Xaa: His, Lys, or Arg) via an amide bond improves the catalytic activity of 1 by increasing its diselenide (Se–Se) reduction potential (E′°). In this study, to modulate the Se–Se redox properties and the association of the compounds with a protein substrate, new catalysts, in which a Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, we evaluated the deiodination activity of an analog (compound 5 [14] ) with glycine (Gly) as a spacer amino acid residue. Instead of Aze and Pro in compounds 3 and 4 , respectively, Gly provides flexibility to the peptide backbone and prohibits the formation of a turn structure [15c] . As a result, substituting Aze and Pro spacers with Gly significantly decreased the ID‐1‐like activity, indicating that the formation of the γ‐turn in the ring‐opened state is essential for promoting deiodination.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we evaluated the deiodination activity of an analog (compound 5 [14] ) with glycine (Gly) as a spacer amino acid residue. Instead of Aze and Pro in compounds 3 and 4 , respectively, Gly provides flexibility to the peptide backbone and prohibits the formation of a turn structure [15c] . As a result, substituting Aze and Pro spacers with Gly significantly decreased the ID‐1‐like activity, indicating that the formation of the γ‐turn in the ring‐opened state is essential for promoting deiodination.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, the family has been expanded to include new members with different structural features, sizes and functions but having the capability to assist in protein folding especially vis-à-vis disulfide bond formation. Owing to this capability, artificial mini proteins have been developed to resemble the PDI-like catalytic activity for promoting the folding process in preparations of peptide-based drugs [ 186 ]. Though PDI proteins are crucial in the normal physiology of the ER by ensuring proper folding and maturation of substrate proteins before they are exported to their destined locations, it has been found that several members of the PDI play roles in cancer as discussed in the review.…”
Section: Discussionmentioning
confidence: 99%